Prospects and challenges for cell-cultured fat as a novel food ingredient. (April 2020) - Fish, Kyle D.; Rubio, Natalie R.; Stout, Andrew J.; Yuen, John S.K.; Kaplan, David L.
Abstract: Background: In vitro meat production has been proposed as a solution to environmental and animal welfare issues associated with animal agriculture. While most academic work on cell-cultured meat has focused on innovations for scalable muscle tissue culture, fat production is an important and often neglected component of this technology. Developing suitable biomanufacturing strategies for adipose tissue from agriculturally relevant animal species may be particularly beneficial due to the potential use of cell-cultured fat as a novel food ingredient. Scope and approach: Here we review the relevant studies from areas of meat science, cell biology, tissue engineering, and bioprocess engineering to provide a foundation for the development of in vitro fat production systems. We provide an overview of adipose tissue biology and functionality with respect to meat products, then explore cell lines, bioreactors, and tissue engineering strategies of potential utility for in vitro adipose tissue production for food. Regulation and consumer acceptance are also discussed. Key findings and conclusions: Existing strategies and paradigms are insufficient to meet the full set of unique needs for a cell-cultured fat manufacturing platform, as tradeoffs are often present between simplicity, scalability, stability, and projected cost. Identification and validation of appropriate cell lines, bioprocess strategies, and tissue engineering techniques must therefore be an iterative process as a deeper understanding of the needs and opportunities for cell-cultured fat develops. Highlights: Cell-cultured fat production is a promising area of cellular agriculture. In vitro fat can be used in cell-cultured meats or as a general food ingredient. Novel cell lines, bioprocess strategies, and scaffold biomaterials are needed.